Confounders for Neonatal Intensive Care Unit Admission ın Neonates of Mothers with Preeclampsia - Kilicci, Cetin; Yayla Abide, Cigdem; Ozkaya, Enis; Bostancı Ergen, Evrim; Yenidede, İlter and Baksu, Neriman Basak and Karakus, Resul and Kucukoglu, Seda (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: The aim of this study was to investigate the effect of some maternal and neonatal clinical parameters on the neonatal intensive care unit admission rates of neonates born to mothers who had preeclampsia. Study Design: Study included 402 singleton pregnant women with preeclampsia who admitted to Maternal-Fetal Medicine Unit of Zeynep Kamil Children and Women’s Health Training and Research Hospital. Pregnancies with uterine rupture, chorioamnionitis and congenital malformations were excluded. Some maternal and neonatal clinical characteristics were assessed to predict neonatal intensive care unit admission. Results: Among 402 neonates, 140 (35%) of them had an indication for neonatal intensive care unit admission, among 140 neonates, 136 (97%) of them were preterm neonates. Comparison of groups with and without neonatal intensive care unit admission indicated significant differences between groups in terms of gestational age, Apgar scores at 1st and 5th minutes, birth weight, some maternal laboratory parameters (Hemoglobin, hematocrit, alanine aminotransferase, aspartate aminotransferase, albumin). In multivariate analysis, among all study population, gestational age at delivery, birth weight and Apgar scores were found to be significantly associated with neonatal intensive care unit admission. On the other hand, in subgroup of term neonates, none of the variables was shown to be associated with neonatal intensive care unit admission. Conclusion: Gestational age at delivery and the birth weight are the main risk factors for neonatal intensive care unit admission of neonates born to mothers who had preeclampsia.